TINJAUAN ATAS PENGAWASAN TERHADAP PERIZINAN PENGUSAHA TEMPAT PENJUALAN ECERAN MINUMAN BERALKOHOL - Dwi Cahyo, Ryan Putra; Adhitama, Satria (Politeknik Keuangan Negara STAN)
ABSTRACT Currently alcoholic drinks are ready on the market. Although it is easy to find alcoholic beverages is a type of beverage that causes negative impacts on consumers, the government needs to impose excise for repairs and repairs to its circulation. This study recommends discussing the implementation of the Supervision of Licensing of Entrepreneurs in the Location of Retail Sales of Alcoholic Beverages in the Office of Supervision and Service of Customs and Excise XXX. This study uses the constructivism paradigm, discussing qualitative with descriptive nature and case study strategies. The informants in this study were several employees at Office of Supervision and Service of Customs and Excise XXX. The results of this study show facts in several stages of licensing not considering the provisions of PMK 201 / PMK.04 / 2008, besides that, because of overseeing Office of Supervision and Service of Customs and Excise XXX XXX against place to sell entrepreneurs who have the intention to spend more than licensed place to sell entrepreneurs in XXX City no longer request the necessary provisions. Keywords: alcoholic beverages, licence number, and excise ABSTRAK Saat ini minuman beralkohol sudah gampang dijumpai di pasaran. Walaupun gampang ditemui minuman beralkohol adalah jenis minuman yang menimbulkan dampak negatif bagi konsumen sehingga pemerintah perlu mengenakan cukai untuk mengatur dan mengawasi peredarannya. Penelitian ini bertujuan untuk menyelidiki pelaksanaan Pengawasan atas Perizinan Pengusaha Tempat Penjualan Eceran Minuman Beralkohol pada Kantor Pengawasan dan Pelayanan Bea dan Cukai XXX. Penelitian ini menggunakan paradigma konstruktivisme, pendekatan kualitatif dengan sifat deskriptif dan strategi studi kasus. Informan dalam penelitian ini adalah beberapa pegawai pada KPPBC XXX. Hasil penelitian ini menunjukkan bahwa dalam beberapa tahapan mekanisme perijinan KPPBC XXX tidak memperhatikan ketentuan PMK 201/PMK.04/2008, selain itu karena kurangnya pengawasan KPPBC XXX terhadap pengusaha TPE yang sudah berijin mengakibatkan hampir setengah dari pengusaha TPE berijin di Kota XXX tidak lagi memenuhi ketentuan yang berlaku. Kata kunci: minuman beralkohol, NPPBKC, DJBC, dan cukai